The complete mitochondrial genome of Euplatypus parallelus (Coleoptera: Curculionidae). Issue 1 (1st January 2017) - Yang, Yan; Wang, Xin-Guo; Li, Ya-Xiao; Liu, Hong-Xia; Chai, Qing-Xiang; Lian, Zhen-Min; Wei, Zhao-Ming
Abstract: Beetles in the weevil subfamily Platypodinae are among the dominant groups of insects in wet tropical forests, which together with bark and ambrosia beetles in the subfamily Scolytinae. Easily recognised by the circle-shaped entrance holes in fallen logs and a very elongated body shape, they have earned the common name, "pinhole borers". All except two Platypodinae species are ambrosia beetles that cultivate fungi in wood tunnels as the sole food for their larvae. Platypodinae is a peculiar weevil subfamily of species that cultivate fungi in tunnels excavated in dead wood. The Platypodinae is likely the oldest known lineage of fungus-cultivating insects, with an origin of the ambrosial habit more than 80 Ma. Here, we sequenced and characterized the complete mitochondrial genome of E. parallelus, which was collected from logs imported from SierraLeone. The complete circular mitochondrial genome (mitogenome) of Euplatypus parallelus is 16, 095 bp in size, containing 37 typical genes and one non-coding AT-rich region. The AT content of the AT-rich region is 87.5%. All protein-coding genes (PCGs) start with standard ATN initiation codons except for nad1 and end with complete termination codons TAA except for cox1 genes using an incomplete stop codon T. tRNA genes are predicted with a characteristic cloverleaf secondary structure except for trnS1 (AGN), whose dihydrouridine (DHU) arm is replaced by a simple loop. The size of the large and small ribosomal RNA genes are 1386 and 741 bp, respectively.